"WALK30X5": a feasibility study of a physiotherapy walking programme for people with mild to moderate musculoskeletal conditions. (June 2020) - Minns Lowe, Catherine J.; Kelly, Paul; Milton, Karen; Foster, Charlie; Barker, Karen
Abstract: Objectives: To explore the feasibility of delivering and evaluating a web-based walking intervention for people with long term musculoskeletal conditions (LTMCs), to determine its acceptability and the feasibility of conducting a definitive trial. Design: Prospective randomised feasibility study, with blind outcome assessment at baseline, 3 and 6 months. Setting: Hospital based physiotherapy service. Participants: Forty one adults referred for assessment and advice for any mild/moderate LTMCs. doing <120 minutes of moderate intensity activity per week. Interventions: Participants randomised to: 1. Usual care: one usual physiotherapy advice and assessment session, including setting a physical activity goal and one follow up session (8 weeks). 2. "Walk30 × 5": session one, usual care plus intervention of walking programme. Participants were shown the website and podcasts and practiced how to use them. One follow up session (8 weeks). Outcome measures: Primary: timed six minute walk test (T6MWT). Secondary: step count, self-reported pain, fatigue, mood, self-efficacy, happiness, objective blood pressure, peak expiratory flow rate, and self-report and accelerometer measured physical activity. Results: Recruitment target achieved. No adverse events occurred. Adherence was high and the intervention acceptable. Loss to follow up n  = 3 (7%) at 3 months, n  = 8 (20%) at 6 months. T6MWT and step count proved suitable outcomes, unlike accelerometry. Estimated sample size for a definitive trial is 216. Conclusions: "Walk30 × 5" is ready for evaluation in a future, appropriately powered ( n  = 216), phase III trial. If effective, the intervention will provide a cheap, highly accessible intervention to enable people with mild/moderate LTMCs to achieve UK physical activity guidelines. Clinical Trial Registration Number: ISRCTN78581097.